Combined treatment of energy-saturated materials in external fields. (March 2020) - Kuzmina, L; Gazenaur, E; Krasheninin, V; Mixel, O; Galtseva, O; Gazenaur, N
Abstract: The paper analyses the effect lead and iron ions have on slow and explosive decomposition in crystals of silver azide initiated by a contact electric filed, local physical impact and UV-radiation. The reaction of decomposition registered immediately in the process of impact was examined according to gas release. This method provides accuracy of 10 −12 mole. A stop-watch was used to determine time-to-explosion. The outcomes of experiments show that introduction of lead and iron ions into crystals of silver azide deteriorates strength of samples under local physical impact; furthermore, gas release caused by this type of impact stimulates fracture of samples. Experimental data indicate that crystals of silver azide with introduced lead and iron tend to decompose more intensively in a contact electric field. As for UV-radiation, it also has a significant decomposing effect on samples with introduced impurity substances, however, no explosion is registered, i.e. a maximal amount of gas is emitted at a certain period of time; afterwards gas release becomes less intensive and stops in approximately 20 minutes after the treatment starts. Any external impact generates misbalanced charge carriers (holes). Holes are localized on cation vacancies associated with generation of reactive centres. The number of reactive centres grows due to the increased concentration of impurity defects and might become critical. Data of experiments suggest that crystals of silver azide with introduced impurities are less stable and chemically inactive in external fields.